Structural variation of transition metal-organic frameworks using deep eutectic solvents with different hydrogen bond donors - Zhao, Ming-Yu; Zhu, Jian-Nan; Li, Peng; Li, Wei; Cai, Ting; Cheng, Fang-Fang; Xiong, Wei-Wei (Dalton transactions : an international journal of inorganic chemistry, 2019)
Deep eutectic solvents (DESs) have attracted extensive attention in the field of material synthesis as green solvents. They have similar physical and chemical properties to the traditional ionic liquids (ILs) while being much cheaper and more environmentally friendly. Herein, seven transition metal-organic frameworks, namely [NH 4 ][Zn(BTC)(NH 3 ) 2 ]·H 2 O ( 1 ), [Cu(PDC)(NH 3 )] ( 2 ), [Co(H 2 BTC) 2 (e-urea) 2 ]·(e-urea)·1/4H 2 O ( 3 ), K 0.63 (NH 4 ) 0.37 [Mn(PZDC)] ( 4 ), [NH 4 ][Mn(BTC)(H 2 O)] ( 5 ), [CH 3 NH 3 ][Mn 3 (HBTC) 2 (BTC)·3H 2 O ( 6 ), and [Co 3 (BTC) 2 (urea) 2 ]·2H 2 O ( 7 ), were synthesized in deep eutectic solvents of choline chloride and urea/e-urea/m-urea (H 3 BTC = 1,3,5-benzenetricarboxylic acid; H 2 PDC = 2,6-pyridinedicarboxylic acid; H 2 PZDC = 3,5-pyrazoledicarboxylic acid; e-urea = ethylene urea; m-urea = N , N -dimethylurea). Of particular interest is the fact that the utilization of different hydrogen bond donors in DES mixtures can lead to the formation of different frameworks. The multiple roles of hydrogen bond donors in the reactions were discussed. Furthermore, compound 7 exhibited catalytic activity for the oxidation of styrene, and thus it can be used as a heterogeneous catalyst due to its good stability. These results promote the understanding of the application of DESs in synthesizing novel transition metal-organic frameworks. Seven transition metal-organic frameworks with structures ranging from one-dimensional chains to three-dimensional networks have been synthesized in deep eutectic solvents.